Bottom-up hierarchical self-assembly of chiral porphyrins through coordination and hydrogen bonds - Oliveras-Gonzalez, Cristina; Di Meo, Florent; Gonzalez-Campo, Arentzazu; Beljonne, David; Norman, Patrick; Maite, Simon-Sorbed; Linares, Mathieu; Amabilino, David A. (American Chemical Society, 2015)
A series of chiral synthetic compounds is reported that show intricate but specific hierarchical assembly because of varying positions of coordination and hydrogen bonds. The evolution of the aggregates (followed by absorption spectroscopy and temperature-dependent circular dichroism studies in solution) reveal the influence of the proportion of stereogenic centers in the side groups connected to the chromophore ring in their optical activity and the important role of pyridyl groups in the self-assembly of these chiral macrocycles. The optical activity spans two orders of magnitude depending on composition and constitution. Two of the aggregates show very high optical activity even though the isolated chromophores barely give a circular dichroism signal. Molecular modeling of the aggregates, starting from the pyridine-zinc(II) porphyrin interaction and working up, and calculation of the circular dichroism signal confirm the origin of this optical activity as the chiral supramolecular organization of the molecules. The aggregates show a broad absorption range, between approximately 390 and 475 nm for the transitions associated with the Soret region alone, that spans wavelengths far more than the isolated chromophore. The supramolecular assemblies of the metalloporphyrins in solution were deposited onto highly oriented pyrolitic graphite in order to study their hierarchy in assembly by atomic force microscopy. Zero and one-dimensional aggregates were observed, and a clear dependence on deposition temperature was shown, indicating that the hierarchical assembly took place largely in solution. Moreover, scanning electron microscopy images of porphyrins and metalloporphyrins precipitated under out-of-equilibrium conditions showed the dependence of the number and position of chiral amide groups in the formation of a fibrillar nanomaterial. The combination of coordination and hydrogen bonding in the complicated assembly of these molecules - where there is a clear hierarchy for zinc(II)-pyridyl interaction followed by hydrogen-bonding between amide groups, and then van der Waals interactions - paves the way for the preparation of molecular materials with multiple chromophore environments.